Administrative and supervisory problems of barrio high schools in the Division of Iloilo - Arsulo, Timoteo C. 1928- ([S.l. s.n.], 1973)
The study identified the problems met by 46 barrio high schools in Iloilo in 1970-71, as perceived by 17 principals, 44 assistant principals and 2 secondary school head teachers. The most urgent administrative problems are (1) inadequacy of funds, (2) late payment of tuition fees, (3) oversized classes in the academic subjects, (4) lack of provincial aid, (5) lack of teachers, and (6) difficulty in the administrative organization. The most urgent supervisory problems are (1) heavy and inappropriate teaching loads, (2) inadequate library and laboratory facilities, (3) inadequate textbooks, references, course of study and teaching guides, and (4) difficulties in upgrading teacher competencies through inservice education. The suggested solutions are improve funding, curricular innovations such as the two-shift plan, team teaching and the In-School-Off-School Approach, and the use of local materials and skills in making apparatus and equipment.
Thesis (M. Ed.)--University of the Philippines.
Typescript.
Keywords: School supervision, Secondary; School management and organization -- Iloilo